Marriage Is Scary Phenomenon In Indonesia: Analysis Of Quranic Response To Increases Marital Violence - Al Faruq, Abdul Qudus; Thobroni, Ahmad Yusam; Sudury, Ahmad Miftahus; Nurkumala, Indah Ayu; Mukminin, Ikhwanul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2025)
The phrase Marriage is Scary resonates in Indonesian society, influenced by rising Marital Violence or KDRT cases. The Central Bureau of Statistics reported a decrease in marriages from 1,695,255 in 2022 to 1,577,255 in 2023. Factors like patriarchal culture and inadequate education contribute to this issue. This study examines the Qur'an's perspective on gender harmony and its role in reducing violence and fostering harmonious households. Using a qualitative, critical-historical approach, the research integrates Asbabunnuzul and Qishshatul Qur’an with a correlational or Munasabah theory by library research method. Findings highlight the Qur'an's emphasis on premarital education, balanced roles between spouses, and prioritizing gender harmony to prevent violence. The study identifies examples of ideal households in the Qur'an, such as the families of Prophet Ibrahim and Imran, illustrating the importance of faith, patience, and mutual cooperation in achieving harmony. In the Indonesian context, where patriarchal norms and increasing marital violence contribute to marital anxiety, this study emphasizes the importance of Qur'anic teachings on justice, mutual respect and premarital preparation for building resilient households.